(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
Persistent Organic Pollutants (POPs) are chemical substances that persist in the environment, bioaccumulate through the food web, and pose a risk of causing adverse effects to human health and the environment. The Stockholm Convention is a global treaty to protect human health and the environment from POPs. In implementing the Convention, Governments will take measures to eliminate or reduce the release of POPs into the environment. This study was done in order to evaluate tentative POPs levels in Lithuania.Limited amount of PAHs and PCBs were analyzed in Šiauliai air, in two biggest Lithuanian rivers – Nemunas and Neris, and in one of the biggest waste landfill in Lapes. Sampling was done using semi permeable membrane devices (SPMDs). The same procedure of sampling and analyses was used to ensure data comparability. In general, POPs pollution levels were compared with results from other studies.